Praktik Monopoli Pada CV Indri Jati Furnitur di Pekanbaru Berdasarkan Undang-Undang Nomor 5 Tahun 1999 - Yetti; Cisilia Maiyori; Yelia Natassa Winstar (Jurnal Hukum Respublica, 2018)
The purpose of this study: First, to explain the application of furniture production and marketing in CV Indri Jati Furniture in the perspective of antitrust law. Second, to analyze the legal consequences of furniture production and marketing applications on CV Indri Jati Furniture in the perspective of antitrust law. This type of research is sociological law, namely the monopolistic practice of CV Indri Jati Furniture in Pekanbaru based on Law no. 5 of 1999. The results of this study indicate that the application of furniture production and marketing at CV Indri Jati Furniture in the perspective of antitrust law is carried out in order to maintain company efficiency in production. However, the vertical integration in fact resulted in unfair business competition by creating competition barriers, as well as harming the community in this case, Karisma Jati Furniture and Rizki Jati Furniture. The legal consequences of a vertical integration agreement for business actors violating the provisions of Law No. 5 of 1999 is the imposition of sanctions for business actors in accordance with statutory provisions, namely administrative sanctions, principal penalties and additional crimes. If the vertical integration results in unhealthy business competition among business actors, the unavailability of access for business competitors to enter the market, a decrease in the quality of goods / products, a waste of money for companies, and no other choices for consumers to buy goods / products.